2 Dashing to recruit faculty. (17th November 2016) - Quayle, Alexandra; Wilson, L; Farooq, O; Trowsdale, L
Abstract : Background: Northern Lincolnshire and Goole NHS Foundation Trust were late adopters of simulation. In July 2015 the Development and Simulation Hub (DaSH) was launched aiming to improve patient safety and quality of care. Simulation requires faculty to help deliver the training 1. To sustain the simulation training DaSH need to recruit faculty to help deliver courses. Methodology: Two successful faculty development days were delivered at both sites, Grimsby and Scunthorpe. Course content included theory and practical sessions such as moulage/debriefing/human factors and writing and running scenarios. Guest speakers included trust executive team and content experts from further afield. Participants included mainly consultants and current educators within the trust, a mix of multi-disciplinary professionals. All staff enjoyed the session and stated their knowledge improved tremendously. Results: Impact: An organisation needs to have the buy-in of the faculty to facilitate learning 2. After the success of the first two faculty development days DaSH aim to deliver faculty development sessions twice a year, at their two main sites. Some people who attended the faculty development days have already taken part in teaching on the simulation sessions provided. To develop, DaSH aims to take feedback from the sessions to improve future faculty development days. DaSH is always looking to expand the team, this will then allow for further simulation to flourish in the organisation.